The Effectiveness of Wordwall-Based Game-Based Learning Model in Islamic Religious Education on Students' Learning Independence at SMPN 12 Padang - Septiani, Rima; Sulaiman, Sulaiman (The Future of Education Journal, 2025)
The process of Islamic Religious Education learning at SMPN 12 Padang still faces several challenges, especially in the aspect of students' learning independence. Some students tend to be passive during lessons, waiting for answers from their classmates due to a lack of understanding of the material, and doubting their own abilities, which leads them to prefer copying others’ answers. This low learning independence affects the students’ learning outcomes. This condition is caused by the learning model, which is less varied and has not been able to create an interactive and enjoyable learning environment. Therefore, an innovative learning model is needed that can foster motivation, activity, and a sense of responsibility among students for their learning process. One relevant model is Game-Based Learning (GBL) using Wordwall, which integrates digital game elements into the learning activities to create a more engaging and meaningful learning experience. This study uses a quantitative approach with a quasi-experimental design of the non-equivalent control group type. The research sample consists of two classes: the experimental class and the control class, with a total sample size of 29. The research instruments include a learning outcomes test and a learning independence questionnaire. Data analysis techniques involve normality tests, homogeneity tests, linearity tests, paired sample t-tests, independent sample t-tests, N-Gain tests, as well as correlation and simple linear regression analyses to test the hypotheses, using SPSS version 27. The results show that the Game-Based Learning model using Wordwall is effective in improving students' learning outcomes and independence. The paired sample t-test produced a significance value of 0.000 (< 0.05) with a mean difference of -13.897, indicating a significant improvement between the pretest and posttest scores in the experimental class. The independent sample t-test showed a significance value of 0.02 (< 0.05), indicating a significant difference between the experimental and control classes. Based on the N-Gain analysis, the average score of 62.43% falls into the category of fairly effective. Meanwhile, the correlation and simple linear regression tests showed a significance value of 0.001 (< 0.05), meaning there is a significant relationship and influence between learning independence and students' learning outcomes. Thus, the alternative hypothesis is accepted, and the Wordwall-based GBL learning model can be an effective alternative to improve students' learning outcomes and independence in Islamic Religious Education.